2015
DOI: 10.1080/21592799.2015.1133266
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 and ROCK2 inhibition alters dendritic spine morphology in hippocampal neurons

Abstract: Communication among neurons is mediated through synaptic connections between axons and dendrites, and most excitatory synapses occur on actin-rich protrusions along dendrites called dendritic spines. Dendritic spines are structurally dynamic, and synapse strength is closely correlated with spine morphology. Abnormalities in the size, shape, and number of dendritic spines are prevalent in neurologic diseases, including autism spectrum disorders, schizophrenia, and Alzheimer disease. However, therapeutic targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 49 publications
3
45
0
1
Order By: Relevance
“…The D’Agostino & Pearson omnibus normality test identified that these spine morphology parameters were not normally distributed, so non-parametric Kolmogorov-Smirnov tests were used. Two-sample Kolmogorov-Smirnov tests compared the frequency of spine morphology among spine populations between each pair of conditions 25, 26 . Additionally, one-way ANOVA with Tukey Post-hoc was performed to compare morphology among conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The D’Agostino & Pearson omnibus normality test identified that these spine morphology parameters were not normally distributed, so non-parametric Kolmogorov-Smirnov tests were used. Two-sample Kolmogorov-Smirnov tests compared the frequency of spine morphology among spine populations between each pair of conditions 25, 26 . Additionally, one-way ANOVA with Tukey Post-hoc was performed to compare morphology among conditions.…”
Section: Methodsmentioning
confidence: 99%
“…; Koleske ; Swanger et al . ). The fine balance between activity of ROCKs and dendritic/synaptic functions is best demonstrated in a study using aged non‐transgenic rats, where treatment with fasudil alone was sufficient to improve spatial learning and working memory (Huentelman et al .…”
Section: Role Of Rocks: Parenchymal Pathologies In Admentioning
confidence: 97%
“…As a key regulator of cytoskeletal proteins, ROCK1/ROCK2 activity is crucial for the structural maintenance of neuronal processes which underlie synaptic transmission and cognitive functions. Over-activation of ROCKs can destabilize dendrites, whereas inhibition of ROCKs can promote neurite sprouting and regeneration (Nakayama et al 2000;Chen and Firestein 2007;Lingor et al 2007;Amano et al 2010;Koleske 2013;Swanger et al 2015). The fine balance between activity of ROCKs and dendritic/synaptic functions is best demonstrated in a study using aged non-transgenic rats, where treatment with fasudil alone was sufficient to improve spatial learning and working memory (Huentelman et al 2009).…”
Section: Cognitive Functionmentioning
confidence: 99%
“…[62][63][64] They have been suggested as potential therapeutic targets for neurodegenerative diseases, including AD. These Ser/Thr kinases are involved in cell motility, cell proliferation, autophagy, and apoptosis.…”
Section: Canet Et Almentioning
confidence: 99%